Financial Sector Assessment : Republic of Korea - International Monetary Fund; World Bank (Washington, DC, 2015)
The initial assessment under the Financial Sector Assessment Program (FSAP) was undertaken in 2003. The first Update mission (April 2013) assessed the observance of selected international standards and codes, and initiated discussions on a broad range of financial sector stability issues. In the case of each of the sector assessments new methodologies adopted since the global financial crisis were employed. The second mission (July 2013) completed its review, documented its assessment in a draft Aide-Memoire, and reviewed with the authorities the Aide-Memoire as well as draft technical notes covering a range of topics. The objectives of the FSAP were to review developments in the financial sector since the initial 2003 FSAP and in light of the lessons from the global financial crisis, assess and formulate recommendations related to financial stability and the financial sector oversight framework. This report presents main findings and recommendations.